The Power of Land Expropriation in the Federation of Ethiopia: The Approach, Manner, Source and Implications - Ganta, Brightman Gebremichael (Bahir Dar University Journal of Law, 2022)
Although the power of land expropriation is arguably an inherent power (I claim it is a constitutional power) of a state in any jurisdiction, the approach, the manner and the source of it varies among nations and is also a point of academic and policy debate. Particularly, in federations, as is the case in Ethiopia, apart from its implication for land tenure security of landholders, it can be also a source of power conflict/competition between the central and state governments. However, the implication of the approach, the manner, and the source of land expropriation power adopted in the Ethiopian land law regime over the land tenure security and central state governments power conflict/competition have not been examined critically. Therefore, this study aims at setting the agenda for academic discourse and legal reform about the approach, the manner and the source of defining the power of land expropriation with the view to enhancing land tenure security and avoiding the potential power conflict/competition between the central and regional governments in the country.